Emprego intermitente: estratégia de enfrentamento à “crise” ou instrumento de precarização das relações de trabalho? - Braz, Narice Flaviana de Souza Alves Barbosa (2020)
Brazil is the scene of “another capital crisis” that caused unemployment and informality to explode, among other damaging consequences. In view of this, it was necessary to adopt strong and urgent solutions, so that the negative impacts arising from this state of affairs could be overcome. In this sense, law 13.467 / 2017 was approved by the Brazilian Parliament with the provision of a new type of employment contract: intermittent. Such contract has an outline that inaugurates a “protective framework” different from that exhibited by the other types of employment contracts hitherto existing, especially with regard to day of work and remuneration, that go on to follow an ultra-flexible pattern. This type of contract, although it appears in a clear moment of attempt to deregulate and relax labor standards, as a result of globalizing capitalism and the weakening of the national regulatory state, falls within a normative framework, which is incompatible with it, which spreads constitutional and social values and of human rights that affirm the dignity of man and the centrality of work as an equalizer of social demands for inclusion in the labor market and equal access to the benefits of the development-fruit of work. In addition, it was intended to undertake a qualitative and quantitative research that would answer the problem question about the extent to which the intermittent employment contract is an effective mechanism in generating decent jobs, as advocated by the Federal Constitution of 1988, Human Rights Treaties in force in Brazil and by the International Labor Organization (ILO). The hypothetical-deductive argument starts from the preliminary data that intermittent hiring lacks requirements that elevate the job created to civilizing levels of dignity and decency that guarantee its validity and conformity as a legitimate instrument to be used to promote full employment. In view of the above, as it could be inferred from the analysis of the data collected, despite generating formal jobs, given that the law categorizes it, the intermittent contract is able to break with the factual-legal requirements of non-eventuality, alterity and onerousness of the employment contract, as well as with the legal-formal requirement of the possible, determined or determinable object, when providing for the possibility of the absence of effective provision of services and payment. So, such a contract distorts the social function of property and its corollary, the social function of contracts, as well as attacks the institutes of freedom to hire and the free expression of autonomy (not of the will, but of the human person), placing the employee intermittent in formal and legal equality with the employer that the former does not boast. In addition, in general, this contract, demonstrates that it does not meet the need to offer and adequately delimit the work of day and remuneration of the worker, hinders access to social security, induces inequalities in the labor market and does not fully respect, nor does it expand spectrum of social protection of the worker. In the intermittent labor relationship there is a disrepute of the social value of work, as it is founded on an economic rationality in which the fundamental rights of workers are pressured below their elementary level. The intermittent employment contract, therefore, is a mechanism that can easily lead the individual to all sorts of deprivation and insecurity, thus not being an effective constitutional and conventional means for generating substantial jobs in Brazil.